From Recognition to Integration: Indigenous Autonomy, State Authority, and National Identity in the Philippines - Nina McMurry (American Political Science Review, 2022)
How does the recognition of collective self-governance rights for indigenous communities affect national unity and state consolidation? In recent decades, many states have recognized such rights, devolving de jure control over land and local governance to indigenous institutions. Prominent perspectives in the state-building literature suggest that these policies are likely to threaten state consolidation by strengthening nonstate authorities at the expense of state authority and subnational identities at the expense of a national identity. Yet few studies have tested whether these policies have the consequences their critics claim. I address this gap, leveraging spatial and temporal variation in the granting of communal land titles to indigenous communities in the Philippines. Using difference-in-differences and panel designs, I find that titling increases both indigenous self-identification and compliance with the state. Results from an original survey experiment suggest that recognizing collective self-governance rights increases identification with the nation.
doi:10.7910/DVN/VW1GDD
Keywords: 320